Effect of Linewidth Enhancement Factor on Fringe in a Self-Mixing Signal and Improved Estimation of Feedback Factor in Laser Diode - Kim, Cholhyon; Lee, Cholman; O, Kwonhyok (IEEE access, 2019)
The optical output power of a laser diode is modulated by the self-mixing effect when the optical beam is back-reflected or back-scattered into the laser cavity by a target. The optical feedback factor C is the most important one that defines the feature of the self-mixing signals (SMSs). And the estimation of C is indispensable for the displacement reconstruction by the phase unwrapping method because it is impossible to reconstruct the displacement with sub-wavelength resolution, provided the exact value of C is unknown. Unfortunately, C is subject to constant change during the measurement and, what is worse; its estimation is usually very time-consuming. This paper studies the feature of a high and low fringe of SMSs in moderate and strong feedback regime and the effect of the feedback factor and the linewidth enhancement factor on the fringes and presents a simple approach to the estimation of C when C > 1.5 based on the behavioral model proposed by Plantier et al. In particular, the novel approach enables fast direct estimation of C because it is based on analytic relations between C and the amplitudes of the high and low peak in SMSs.